Positron Annihilation Spectroscopy of Defects in Commercially Pure Titanium Saturated with Hydrogen - Laptev R. S. Roman Sergeevich; Bordulev Yu. S. Yuri Sergeevich; Kudiyarov V. N. Victor Nikolaevich; Lider A. M. Andrey Markovich; Garanin G. V. Georgy Viktorovich (Diagnostics and Engineering of Novel Materials, 2014)
Title screen